Sleep apnea is associated with stroke in young patients with or without atrial fibrillation:A population study of >2 million individuals. (19th May 2022) - Deb, B; Vasireddi, SK; Clopton, P; Ganesan, P; Feng, R; Rogers, AJ; Baykaner, T; Bhatia, NK; Narayan, SM
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): NIH, R01 HL149134, R01HL83359 Background: Both Sleep Apnea (SA) and Atrial Fibrillation/flutter (AF) are known risk factors for stroke, and both are increasing in prevalence. They are both under-diagnosed in young adults <60 Y. There is an urgent need to define stroke risk portended by SA and AF yet there a paucity of data in adults aged 20-60 years. Purpose: To define the relationship between stroke, SA, and AF in a very large cohort of 2 million young-middle aged adults aged 20-60 Y in Northern California. Methods: We probed the Stanford Research Repository of electronic health data from 01/01/2008 to 11/30/2021 for the diagnoses of stroke, transient ischemic attacks, AF and SA using relevant codes (stroke: 433.X, 434.X, 436.X, I63.X, I65.X, I66.X, G45.X, G46.X; AF: I48.X; SA: G47.X, 327.27). Results: We identified 2267485 patients aged 20-60Y (55% F; 32% White, 12% Asian, 3% Black), of whom SA was diagnosed in 52730 (2.3%), AF in 10230 (0.4%) and incident stroke in 10385 (0.4%) (Figure 1A) In patients with SA, 1.5% developed incident stroke. Stroke was more common in patients with SA than those without, regardless of co-existing diagnosis of AF; OR with AF: 1.5 [1.3-1.7, p<0.001] and OR without AF: 3.0 [2.8-3.3 p<0.0001]. Risk of stroke with SA than without was noted to be higher in the younger age subgroups (Figure 1B) regardless of AF. Although AF was more common in patients with SA than without (odds ratio, OR: 10.1 [9.6-10.6, p<0.0001]), the majority of SA patients (63% with CHADS2VASC ≥2) with stroke did not have a diagnosis of AF (75%), of whom 96% were not anticoagulated (Fig 1, left panel). Of the remaining patients with SA and incident stroke, who did have AF (25%), only 26% were taking OACs at the time of stroke despite median CHADS2 VASC score=3 (Fig 1A, left panel). Finally, 7% of AF patients developed incident stroke. Of these, 73% had CHADS2VASC ≥2, yet 44% were not anticoagulated. Patients with SA comprised a third of all AF patients with stroke and, compared to AF patients with stroke and without SA, had higher CHADS2VASC (median 3 vs 2, p<0.001) and a similarly low use of anticoagulation (56% vs 54% on OAC) (Fig 1A, right panel). Conclusions: In >2 million young individuals, we uncover a novel association between SA and incident stroke, regardless of the diagnosis of AF. Surprisingly, three quarters of patients with SA developed incident stroke in the absence of AF, and were not anticoagulated. These results underscore the need to screen for AF and sleep apnea in young adults.